Stem protective tissue in Erythroxylum tortuosum (erythroxylaceae), a fire tolerant species from cerrado - Alonso, Alexandre Antonio [UNESP]; Machado, Silvia Rodrigues [UNESP] (Brill Academic Publishers, 2008)
The origin and structure are described of the secondary protective tissue in the stem of Erythorxylum tortuosum Mart., a fire tolerant shrubby species common in Brazilian cerrado. The highly tortuous stems are covered with thick bark which is more developed at the base of the stem. After fire in the cerrado, rhytidome fragments of the burned stem flake off, revealing newly formed cork. The first periderm appears near of the terminal buds and is iniated by periclinal divisions in subepidermal cells giving rise to radial rows of cells. The first phellogen is discernible only after the differentiation of the several radial rows of cork cells. Other phellogens have their origin in successively deeper layers of the cortex. The sucessive periderms are discontinuous around the circumference. The collapsed cells with phenolic substances and the accumulated dead cells cause the formation of discontinuous blackish lines, which delimit the sucessive periderms in the rhytidome. The rhytidome contains large quantities of sclereids developed from cell wall thickening of cortex cells. The occurrence of periderm in the young parts of the stem and of rhytidome in the older parts represents pyrophytic characteristics and may explain, in part, the fire tolerance of this species.
Keywords: Bark; Cerrado; Erythroxylum tortuosum; Fire tolerant species; Periderm; Rhytidome; Stem